Awareness, attitudes towards plagiarism, and acceptance of using Turnitin in academic writings among undergraduate students - Wan Zumusni Wan Mustapha; Nur Fadhlina Zainal Abidin; Tuan Sarifah Aini Syed Ahmad; Irma Ahmad; Sheela Paramasivam (Universitas Syiah Kuala, 2023)
The purpose of this study was to examine the association of awareness of plagiarism, attitudes towards plagiarism and acceptance of using Turnitin among undergraduate students in a public university. The study was conducted on 143 undergraduate students at Universiti Teknologi MARA, Negeri Sembilan campus. Data was collected using an online questionnaire in the Google Form platform. These students took the Academic Writing subject. The ordinal data were collected using the 5-point Likert Scale. By studying the normality of the data using Kolmogorov-Smirnov and Shapiro-Wilk statistical tests, the association between awareness of plagiarism, attitudes towards plagiarism, and acceptance of using Turnitin, can be made. The tests compared the sample's scores to a normally distributed set of scores with the same mean and standard deviation. This paper presents the major findings from non-parametric correlations (Spearman’s rank-order and Kendall Tau-b) and suggests future research direction in increasing undergraduates’ awareness of plagiarism and awareness of using Turnitin when submitting their academic assignments. To curb plagiarism among undergraduates in an academic writing course, the authors propose a plagiarism policy within academic institutions, strict sanctions on plagiarism, and teach students how to avoid plagiarism and the use of Turnitin.